Further development and testing of a bimodal aerosol dynamics model - Youngblood, Debra A., author; Kreidenweis, Sonia M., author (Colorado State University. Libraries, 1994)
A previously reported bimodal monodisperse aerosol model is further developed and tested. The starting point is the BImodal MOnoDisperse Aerosol Model (BIMODAM I) which was developed to model the formation of ammonium sulfate ((NH4) 2SO4) particles from sulfuric acid (H2SO4) vapor. The model follows the evolution of two monodisperse modes where each mode, i, is characterized by a unique mean diameter and the number of particles with that mean diameter. The aerosol distribution is assumed to undergo typical atmospheric processes such as condensational growth, coagulation, nucleation, and deposition. In BIMODAM I, the effect of each process on the aerosol distribution is represented as a rate equation. The prognostic equations are coupled, so a variable time step differential equation solver is utilized to simultaneously solve the system of equations to predict the mass and number concentration in each mode. The diameter of each mode is diagnosed from the mass and number concentrations. In the first part of this work, two new parameterizations were developed for BIMODAM I. First, a condensation rate factor was developed to account for the lack of polydispersity in the model. Second, a criterion was developed which dictates when the two modes may be merged without generating large errors. In the second part of this work, a new version of the model (BIMODAM II) was developed to give the same accurate results as BIMODAM I without using the variable time step differential equation solver. A key development in BIMODAM II is a parameterization for the process of homogeneous nucleation. This parameterization is based on the approximation of the time-dependent nucleation rate with a triangular function; using this approach, only two parameters are needed to predict the total number of particles resulting from a nucleation event The two parameters are correlated to chemical source rate and relative humidity. Therefore, prediction of the number concentration of particles resulting from a nucleation burst depends on knowing the relative humidity and determining the chemical source rate. This development has been shown to perform well in the presence and absence of preexisting particles and over short and long time scale simulations. Further developments in BIMODAM II include simple analytical solutions of the differential equations for coagulation and deposition. Using a mass balance equation, a simple solution was also derived to predict the amount of sulfuric acid in the vapor phase at any time during the simulation. From this calculation, the amount of mass in the aerosol phase is calculated by subtracting the amount in the vapor phase from the total amount of sulfuric acid produced during any given time step. By using the simplifications and parameterizations mentioned above, computational time is saved by eliminating the variable time stepping differential equation solver. This model is shown to perform well when compared against a simulation which uses a more detailed description of the aerosol size distribution.
April 1994.
Also issued as Debra A. Youngblood's thesis (M.S.)- Colorado State University, 1994.
Keywords: Aerosols -- Climatic factors; Climatic changes